2013
DOI: 10.1063/1.4819798
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy-type defects introduced by plastic deformation of GaN studied using monoenergetic positron beams

Abstract: Vacancy-type defects in plastically deformed GaN were studied using monoenergetic positron beams. Dislocations with a Burgers vector of (1/3)[1 210] were introduced by applying compressive stress at 950 C. Measurements of Doppler broadening spectra of the annihilation radiation and positron lifetime spectra showed that both microvoids and Ga-vacancy-type defects were introduced into the deformed sample. The former defects are considered to be introduced through an agglomeration of vacancies introduced by dislo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…The longest lifetime was obtained at 500–550 ps. A similarly long positron lifetime was observed for plastically deformed GaN, attributing to positron trapping by large vacancy clusters or microvoids. For the present samples, the open spaces adjacent to secondary defects are also candidates as positron trapping centers.…”
Section: Resultssupporting
confidence: 54%
“…The longest lifetime was obtained at 500–550 ps. A similarly long positron lifetime was observed for plastically deformed GaN, attributing to positron trapping by large vacancy clusters or microvoids. For the present samples, the open spaces adjacent to secondary defects are also candidates as positron trapping centers.…”
Section: Resultssupporting
confidence: 54%
“…Details of the growth procedure of BaSi 2 films were reported previously. [17][18][19][20][21][22][23] During the MBE growth, R Si was fixed to be 0.9 nm min −1 and R Ba was varied from 0.9 to 3.2 nm min −1 , giving a variation of R Ba /R Si from 1.1 to 3.6. In this study, we also conducted MBE at 650 °C, which is 70 °C higher than the temperature used in our previous experiments.…”
mentioning
confidence: 99%
“…Through this method, vacancy-type defects of various semiconductors (i.e., GaN, AlON x , CIGS) have been investigated. [22][23][24][25][26] Figure 1(a) shows the S parameters of BaSi 2 films grown at T S = 580 °C with various R Ba /R Si . We found that the optical properties changed markedly as R Ba /R Si values were varied, and the maximum photoresponsivity was achieved at R Ba /R Si = 2.2 for samples grown at T S = 580 °C, as shown in Fig.…”
mentioning
confidence: 99%
“…(i) defect/pore analysis of small samples [10][11][12][13][14][15][16] (ii) defect/pore analysis for many local spots in large samples [3,[17][18][19] (iii) in-situ (in-air) defect/pore analysis of thin films [20,21] In the present study a new analytical method which we call the combinatorial technique is described. This combinatorial defect/pore analytical method can be categorized as follows;…”
Section: Introductionmentioning
confidence: 99%